DISEMINASI MESIN TANAM PADI BAGI KELOMPOK TANI DALAM MENDUKUNG SWASEMBADA PANGAN DI KABUPATEN LAMONGAN - Mu’tamar, M. Fuad Fauzul; Hidayat, Khoirul; Yaskun, Mohammad (ABIDUMASY, 2025)
Food self-sufficiency is a priority program of the central government, and Lamongan Regency, as the largest rice producer in East Java, contributing 8.2% of the province's total production, plays a crucial role. However, challenges include a declining workforce, high cost of rice planting machines, and short seedlings, typically 10-13 cm in length. This requires water to be removed during planting until the seedlings reach a height of around 20 cm. This leads to overgrowth of grass, as the rice seeds are not adequately irrigated. To address these issues, it is necessary to disseminate appropriate technology, specifically the rice transplanter machines, to increase crop productivity. The method used is action research, which involves taking action based on observations and discussions with partners. The results of this activity indicate that the use of rice planting machines can increase crop productivity from 0.1 ha/day to 1.15 ha/day, an 11-fold increase. It is hoped that the rice transplanter machine will help farmers overcome the decreasing number of workers and support the government's food self-sufficiency, especially in Lamongan Regency, which is one of the rice-producing areas in East Java.